The Buddha's system of meditation : phase three : the supernormal powers - Pradhan, Ayodhya Prasad (Oriental University press)
The Buddha's System of Meditation, Phase I-VIII**
Includes bibliographic references.
Keywords: Buddhism; Meditation -- Buddhism; Yoga